(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2018)
This study describes a set of efforts to develop training evaluation measures. The methodological challenges are discussed for each of these levels of evaluation and some examples of how the analysis and measurement problems have been solved. It is a theoretical survey of the state of the art in this field and describes the most important and recognized models of impact assessment training. It will be a reflection on the methodological array of training evaluation and discusses the conditions for the implementation of the ROI methodology. Data were obtained through the application of an online survey conducted for professional training area and the management of human resources, showing the actual progress of the assessment of the impacts of training in organizations. These results showed that the motivation of supervisors and managers is in first place on the factors that mostly influenced the success of a training and that the training plan is the result of a diagnosis of training needs and is not aligned with a performance appraisal system and that despite the ROI methodology to be chosen as the one that would like to apply kirkpatrick model is mostly used by companies because of the cost associated with implementation of the ROI methodology.